Uranyl-containing heterometallic coordination polymers based on 4-(4'-carboxyphenyl)-1, 2, 4-triazole ligand: structure regulation through subtle changes of the secondary metal centers. Issue 16 (17th September 2018) - Zhao, Ran; Mei, Lei; Hu, Kong-Qiu; Wang, Lin; Chai, Zhi-Fang
Abstract: Three uranyl-containing coordination polymers, Cd(UO2 )2 (cpt)4 (bdc)(H2 O)2 (1 ), Zn(UO2 )2 (cpt)4 (bdc)(H2 O)2 (2 ) and UO2 (OH)(cpt) (3 ) (Hcpt =4-(4'-carboxyphenyl)-1, 2, 4triazole, H2 bdc =1, 4-benzenedicarboxylic acid), have been synthesized under hydrothermal conditions by employing a bifunctional ligand (Hcpt) with both O-donors and N-donors. Compound1 represents a 3-D framework with the point symbol of (6 2 ·8 4 )(6 2 ·8)2 by the intersection of two sets of 1-D [Cd2 (UO2 )2 (cpt)4 (bdc)]n loop chains extended along different directions. Compound2 exhibits a 2-nodal (3, 4)-connected 2-D network with the point symbol (4·6 2 )2 (4 2 ·6 2 ·8 2 ). Compound3 shows a 2-D network by the assembly of uranyl dimers and the cpt - anions. Although1 and2 have similar chemical formulas and the same coordination modes of ligands and metal centers, they possess totally different molecular frameworks, derived from the different radii of the secondary metal centers, Cd(II) and Zn(II). In addition, the optimal synthesis condition, thermal stability, luminescent properties, and IR spectra of1 and2 were also investigated. Graphical Abstract: